Comparative analysis of technical efficiency on different management systems of irrigation schemes in Limpopo Province, South Africa : a stochastic frontier production approach - Hlongwane, Johannes Jan (My University, 2015)
Various types of management practices/institutional arrangements of the irrigation schemes exist in the world. According to the principles delineated in literatures, these irrigation schemes are categorized in terms of their management practices. The study was designed to compare the level of technical efficiency of farmers at different management practices of the irrigation schemes (i.e. integrated, specialised and multipurpose water management practices of the irrigation schemes) in Limpopo Province. Data were collected using a structured questionnaire which was administered on 200 farmers at different irrigation schemes. Stochastic frontier production function of Cobb-Douglas type was employed to analyse the data and thereby ascertain the level of technical efficiency and its determinants. The results indicated the mean technical efficiency of 0.74, 0.72 and 0.76 for the integrated, specialised and multipurpose water management practices of the irrigation schemes respectively which implied that, there is a greater scope to increase maize, tomato, onion and spinach production with the current technology and resources available at the irrigation schemes. The most important contributors in maize, tomato, onion and spinach production efficiencies were seed, fertilizer, capital and land. Thus an appropriate amount of seed, fertilizer, capital and land could increase the productivity of maize, tomato, onion and spinach. The results further revealed that education level of farmers, age of the farmers and land size were negatively significant toward the technical inefficiency of farmers at different irrigation schemes, which imply that an increase in any of the three variables will reduce the inefficiency and enhance the efficiency. While the family size of the farmer was positively significant, which implies that the bigger the family size, the higher the inefficiency farmers would become for the production of maize, tomato, onion and spinach. Gender and income level of the farmers at different irrigation schemes were revealed to be insignificant toward the inefficiency. The institutional arrangements or the management practice of the irrigation schemes showed slight differences in affecting the efficiency of farmers at different irrigation schemes. Policies designed to educate famers at different irrigation schemes through proper agricultural extension services could have a great impact in increasing the level of efficiency and hence maize, tomato, onion and spinach productivities. The Department of Agriculture should allocate more funds to strengthening the extension directorate and expanding the delivery of extension services to farmers at different irrigation schemes. Irrigation schemes were established in order to insure food security, alleviate poverty, job creation, among others. Therefore, it is of paramount importance for the government of South Africa in collaboration with the private sector to revitalise the irrigation schemes in Limpopo Province irrespective of the institutional arrangements. It is of vital concern for the policy makers to focus on the benefits of economies of scale in agricultural farming system. Therefore, land size should be increased for the farmers in integrated water management practice of the irrigation schemes to an optimum level in order for them to improve the level of technical efficiency.
Thesis (Ph.D. (Agricultural Economics)) -- University of Limpopo, 2015
Keywords: Irrigation Schemes; Irrigation systems management practices; Irrigation efficiency -- South Africa; Irrigation -- South Africa -- Limpopo; Buildings -- Irrigation systems; Irrigation -- Management